Pengaruh Online Customer Review (Ocr) Dan Hedonic Shopping Motivation Terhadap Impulse Buying Yang Dimediasi Oleh Brand Trust Pada E-Commerce Brand Skintific (Studi Kasus Pada Mahasiswi Unisma) - Rochmatulloh, Dewanty; Rachma, N.; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study was conducted to determine the effect of Online Customer Review (OCR) and Hedonic Shopping Motivation on Impulse Buying mediated by Brand Trust on e-commerce Brand skintific. This study uses a quantitative approach with an explanatory research type. The population of the study were students of the University of Islam Malang who shopped for skintific products on e-commerce, with a sample of 95 respondents selected using the non-probability sampling technique with a purposive sampling and snowball sampling approach. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS 4.1.0.9 software. The results of this study indicate that Online customer reviewhas an effect on Brand Trust, hedonic shopping motivation has an effect on brand trust, Online customer reviewhas an effect on impulse buying, Hedonic shopping motivation has no effect on impulse buying, Brand Trust has an effect on impulse buying, Online customer reviewhas no effect on impulse buying through brand trust and hedonic shopping motivation has an effect on impulse buying through brand trust. Keywords: Online Customer Review, Hedonic Shopping Motivation, Impulse buying, Brand Trust